2009
DOI: 10.1051/0004-6361/200911721
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution study of isotopic composition and chemical abundances of blue horizontal branch stars in the globular clusters NGC 6397 and NGC 6752

Abstract: Aims. Large abundance anomalies have been previously detected in Horizontal Branch B-type stars. It has been suggested that at T eff > 11 000 K the stellar atmospheres become susceptible to diffusion effects and thus develop surface abundances similar to those that appear in the main-sequence, chemically peculiar group of A and B-type stars. We present the first high-resolution study of isotopic anomalies and chemical abundances in six Horizontal Branch B-type stars in globular clusters NGC 6397 and NGC 6752 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
(65 reference statements)
2
17
0
Order By: Relevance
“…1 Borra et al (1983). It is however possible that Feige 86 exhibits more similarity with HgMn stars than with sdB stars, as it shows He and Hg isotopic anomalies (Hubrig et al 2009). …”
Section: Observations and Magnetic Field Measurementsmentioning
confidence: 99%
“…1 Borra et al (1983). It is however possible that Feige 86 exhibits more similarity with HgMn stars than with sdB stars, as it shows He and Hg isotopic anomalies (Hubrig et al 2009). …”
Section: Observations and Magnetic Field Measurementsmentioning
confidence: 99%
“…They detected vertical Fe stratification in five (and possibly seven) of these BHB stars. Isotopic anomalies have also been recently detected in BHB stars (Hubrig et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Vertical stratification of iron abundance was also detected by Khalack et al (2008) in the atmosphere of two BHB stars in the globular cluster M15 and for one star in the globular cluster M13. Furthermore, more recently, Hubrig et al (2009) have found isotopic anomalies of calcium in six BHB stars.…”
Section: Introductionmentioning
confidence: 95%